Role of infrastructures in explaining trade costs in ASEAN 5 - Ramli, Mohd Khairul Rafiz; Ismail, Normaz Wana (Kaunas University of Technology, 2014)
Numerous studies have shown that infrastructure has a positive impact on international trade. For instance, benefit of infrastructure can be shared with many stakeholders especially with the poor ones in a remote area. Hence, a good infrastructure can lower market access restriction, opportunity costs and increase the likelihood of participating in the benefit of international trade. However, existing studies have mainly focused on the traditional determinants of trade costs such as distance and border effects overtime. The role of infrastructure towards trade costs was largely overlooked. Infrastructure is not just limited to public utilities but also includes information and communication technology (ICT), political and social network, and some aspect of soft infrastructure such as management practice, operating procedures and policies development. Some studies proved that infrastructure has significant and relatively large impact on trade flows especially in telecommunication infrastructure. Infrastructure development is important as a tool to speed up the economic integration within the region particularly in the area of international trade and investment. Efficient infrastructure can expand linkages to supply chain by lowering trade costs and increasing value added that is translated into potential profitability. As infrastructure expands, it motivates regional cooperation in infrastructure development, intraregional trade and broadens the investment that eventually lower the trade costs among countries. Following recent empirical studies that emphasize the importance of infrastructure, this paper examines the role of infrastructure in explaining trade costs in ASEAN-5 member countries namely Malaysia, Indonesia, Philippines, Singapore and Thailand. Arguably, countries with good infrastructure will have less trade costs and this empirical study aims at shedding a light on the role of infrastructure towards trade costs by grouping infrastructure into four types which are land, sea, air and ICT and utilities infrastructures. The rationale behind this is that this approach allows us to disentangle and estimate the role of the different modes of infrastructure towards trade costs. The analysis is based on panel data from 1980 to 2009. There are several important conclusions emerging from this analysis. First, in full sample observation, internet appears to be the most deterministic variable of trade costs in ASEAN-5. This finding is congruent with the view that the better the ICT infrastructure the more accessible information about the foreign market the traders will gain thus decreasing the costs to trade. In separate model, rail route significantly decreases trade costs in these regions. This support the empirical results that improvements in basic infrastructure increase the accessibility of goods form producer to consumer thus, lowering the trade costs significantly. Others such as paved road, energy, gasoline and diesel consumption used in road sector are equally important in explaining the trade costs through these regions.